A construção verbal V1Dar + preposição + V2infinitivo: um estudo na interface Sociolinguística e Gramaticalização - Silmara Eliza de Paula Silva (2018)
This research analyzed 1,141 occurrences of the verb DAR, in the Portuguese languagefrom the 18th to the 19th century, collected in the Corpus do Português site, with the following search syntax: VDAR + PREPOSITION + VINFINITIVE.The results obtained led us to three types of occurrences of the verb that is the object of our study:(i) as a predicator, in the context of purpose; (ii) as auxiliary verb, in aspectual constructions and (iii) in modal constructions.Aiming to deepen studies already developed with the same verb by Coelho and Silva (2014) and Coelho (2017) on the legacy of the Latin language in the process of grammaticalization of constructions in Portuguese, we devoted ourselves to investigate whether the analyzedaspectual constructions in the process of grammaticalization and the motivations for the incorporation of the aspectual values in this construction. We also look for answers that justify the existence of a variation between the prepositions "de" and "para" in aspectual constructions inchoative and iterative and the reason for such a variation not to occur with modal ones.Finally, we dedicated to investigating the origin of the prepositions present in such constructions. To answer such questions, we sought a theoretical support in the model fromConstruction Grammar (GOLDBERG, 1995), and we adopted an interface methodology between grammaticalization of constructions and Labovian sociolinguistics (NEVALAINEN and PALANDER, 2012; POPLACK, 2012).Thus, starting from the hypothesis that a process of specialization of uses seems to occur, which allows a given function to arise to fulfill certain purposes,we found that from a semantic specialization of forms, modal and aspectual constructions started to demand certain prepositions and to occur in a more specific context, which converges with one of the principles of grammaticalization, according to which when the more an item is grammaticalized, the more it reduces its syntagmatic variability andthe more its use becomes mandatory in certain contexts.